A contingent perspective on the synergistic effect of governance mechanisms on sustainable supply chain. Issue 3 (11th June 2018) - Ni, Wenbin; Sun, Hongyi
Abstract : Purpose: Literature proposes that implementing supplier assessment and supplier collaboration simultaneously may lead to better sustainable performance. The purpose of this paper is to empirically examine the proposition by considering the contingent effects of two contextual factors, the environmental dynamism and the stakeholder pressure on sustainability. Design/methodology/approach: Four configurations of governance mechanisms are identified according to the different levels of implementing supplier assessment and supplier collaboration. The performances of the four configurations are compared against the levels of environmental dynamism and stakeholder pressure. The empirical data from the sixth round of International Manufacturing Strategy Survey (IMSS) are used. Findings: This paper found that the governance configuration with the highest level of implementing both governance mechanisms leads to the best performance. The synergistic effect that supplier assessment and collaboration complement each other to achieve better performance is verified. However, the synergistic effect holds robust only when the environmental dynamism and stakeholder pressure are high. The synergistic effect vanishes in the social and environmental performance when the environmental dynamism is low. The effect also vanishes in the environmental performance when the stakeholder pressure is low. No synergistic effect was found in business performance. Originality/value: This paper reveals the complementarity between supplier assessment and supplier collaboration when they are implemented at a reasonably high level. It also reveals the importance of the fit of governance mechanisms under different external contexts. The results contribute to reconciling the disputes about the effectiveness of governing supplier relationship to achieve the sustainability along a supply chain.